2011
DOI: 10.1160/th10-05-0307
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe factor XI deficiency have a reduced incidence of deep-vein thrombosis

Abstract: Factor XI (FXI) plays a dual role in haemostasis and thrombosis. It contributes to thrombin generation and promotes inhibition of fibrinolysis. Severe FXI deficiency was shown to confer protection against arterial and venous thrombosis in animal models without compromising haemostasis. We have previously shown that patients with severe FXI deficiency have a low incidence of ischaemic stroke, but display the usual incidence of myocardial infarction. In the present study, we compared the incidence of deep-vein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(174 citation statements)
references
References 40 publications
(52 reference statements)
8
156
1
2
Order By: Relevance
“…22 The reduced risk of VTE associated with factor XI deficiency is in line with a previous study that observed not 1 case of DVT among 219 adults with severe factor XI deficiency, a finding that was significantly different from the expected number of DVTs from a population-based cohort. 12 In our study, however, the observation that no patient with moderate to severe factor XI deficiency had a VTE event and the observed reduced risk of VTE with mild factor XI deficiency suggest a dose-response relationship between factor XI deficiency and VTE. These findings are supported by the results of a randomized controlled trial that compared enoxaparin with 2 different dosages of factor XI antisense oligonucleotide that specifically reduced factor XI levels, in patients undergoing elective unilateral total knee arthroplasty.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…22 The reduced risk of VTE associated with factor XI deficiency is in line with a previous study that observed not 1 case of DVT among 219 adults with severe factor XI deficiency, a finding that was significantly different from the expected number of DVTs from a population-based cohort. 12 In our study, however, the observation that no patient with moderate to severe factor XI deficiency had a VTE event and the observed reduced risk of VTE with mild factor XI deficiency suggest a dose-response relationship between factor XI deficiency and VTE. These findings are supported by the results of a randomized controlled trial that compared enoxaparin with 2 different dosages of factor XI antisense oligonucleotide that specifically reduced factor XI levels, in patients undergoing elective unilateral total knee arthroplasty.…”
Section: Discussioncontrasting
confidence: 66%
“…11 Because factor XI displays both procoagulant and antifibrinolytic activities, it has been postulated that an underlying cardiovascular benefit may protect factor XI-deficient subjects. Small studies showed that severe factor XI deficiency is associated with reduced incidences of deep vein thrombosis 12 and ischemic stroke, 13 but not with myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In a study of adult fXI-deficient patients in Israel, the rate of DVT (0/219) was statistically lower than the expected rate in the matched general population. Conversely, elevated fXI antigen levels were found to be a risk factor for VTE in the LITE study, with an odds ratio (OR) for VTE with fXI levels in the top quintile of 1.8 [95% confidence interval (CI), 1.3-2.7].…”
Section: Fximentioning
confidence: 90%
“…28,29 Patients with severe deficiency of factor XI, the substrate for activated FXII, have a reduced incidence of DVT. 30 Naturally occurring polyphosphates such as extracellular DNA, RNA, and inorganic polyphosphate are potent activators of the coagulation cascade ( Fig. 1) and represent a potential therapeutic target for novel anticoagulation strategies.…”
Section: The Vessel Wall and Coagulationmentioning
confidence: 99%